Nanoconfined LiBH4 as a Fast Lithium Ion Conductor. (22nd October 2014) - Blanchard, Didier; Nale, Angeloclaudio; Sveinbjörnsson, Dadi; Eggenhuisen, Tamara M.; Verkuijlen, Margriet H. W.; Suwarno; Vegge, Tejs; Kentgens, Arno P. M.; de Jongh, Petra E.
<x xml:space="preserve">Abstract</x> Designing new functional materials is crucial for the development of efficient energy storage and conversion devices such as all solid‐state batteries. LiBH4 is a promising solid electrolyte for Li‐ion batteries. It displays high lithium mobility, although only above 110 °C at which a transition to a high temperature hexagonal structure occurs. Herein, it is shown that confining LiBH4 in the pores of ordered mesoporous silica scaffolds leads to high Li+ conductivity (0.1 mS cm−1) at room temperature. This is a surprisingly high value, especially given that the nanocomposites comprise 42 vol% of SiO2. Solid state 7Li NMR confirmed that the high conductivity can be attributed to a very high Li+ mobility in the solid phase at room temperature. Confinement of LiBH4 in the pores leads also to a lower solid‐solid phase transition temperature than for bulk LiBH4. However, the high ionic mobility is associated with a fraction of the confined borohydride that shows no phase transition, and most likely located close to the interface with the SiO2 pore walls. These results point to a new strategy to design low‐temperature ion conducting solids for application in all solid‐state lithium ion batteries, which could enable safe use of Li‐metal anodes.